Marco Túlio Cícero: concepções do discurso religioso no final da República romana - Oliveira, Isadora Buono [UNESP] (2014)
The aim of this paper is to analyze the specifics of the Roman religion as an element of this religious discourse in the works of Marcus Tullius Cicero that have philosophical-religious nature: On the Nature of the Gods, On Divination, On the Laws and the speech On his House. The sources grouped immeasurable elements for understanding the debates on the Roman Religion in the first century BCE. Thus, the religious aspect is evidenced by emphasizing the traditional as it is a better means of maintaining order in relation to the aristocracy. These sources allow to contemplate the perception of Cicero on Religion, that is to establish the traditional character emphasized as opposed to foreign cults increasingly present with the expansion of the Imperium. Meanwhile, sources also allow the perception of social and intellectual exponents involved in religious and political discourse ramifications in the late period of the Roman Republic